Competitive Antagonism of Anesthetic Action at the γ-Aminobutyric Acid Type A Receptor by a Novel Etomidate Analog with Low Intrinsic Efficacy. (November 2017) - Ma, Celena; Pejo, Ervin; McGrath, Megan; Jayakar, Selwyn S.; Zhou, Xiaojuan; Miller, Keith W.; Cohen, Jonathan B.; Raines, Douglas E.
Abstract : Background: The authors characterized the γ-aminobutyric acid type A receptor pharmacology of the novel etomidate analog naphthalene–etomidate, a potential lead compound for the development of anesthetic-selective competitive antagonists. Methods: The positive modulatory potencies and efficacies of etomidate and naphthalene–etomidate were defined in oocyte-expressed α1 β3 γ2L γ-aminobutyric acid type A receptors using voltage clamp electrophysiology. Using the same technique, the ability of naphthalene–etomidate to reduce currents evoked by γ-aminobutyric acid alone or γ-aminobutyric acid potentiated by etomidate, propofol, pentobarbital, and diazepam was quantified. The binding affinity of naphthalene–etomidate to the transmembrane anesthetic binding sites of the γ-aminobutyric acid type A receptor was determined from its ability to inhibit receptor photoaffinity labeling by the site-selective photolabels [ 3 H]azi-etomidate and R-[ 3 H]5-allyl-1-methyl-5-(m-trifluoromethyl-diazirynylphenyl) barbituric acid. Results: In contrast to etomidate, naphthalene–etomidate only weakly potentiated γ-aminobutyric acid–evoked currents and induced little direct activation even at a near-saturating aqueous concentration. It inhibited labeling of γ-aminobutyric acid type A receptors by [ 3 H]azi-etomidate and R-[ 3 H]5-allyl-1-methyl-5-(m-trifluoromethyl-diazirynylphenyl) barbituric acid with similar half-maximal inhibitory concentrations of 48 μM (95% CI, 28 to 81 μM) and 33 μM (95% CI, 20 to 54 μM). It also reduced the positive modulatory actions of anesthetics (propofol > etomidate ~ pentobarbital) but not those of γ-aminobutyric acid or diazepam. At 300 μM, naphthalene–etomidate increased the half-maximal potentiating propofol concentration from 6.0 μM (95% CI, 4.4 to 8.0 μM) to 36 μM (95% CI, 17 to 78 μM) without affecting the maximal response obtained at high propofol concentrations. Conclusions: Naphthalene–etomidate is a very low-efficacy etomidate analog that exhibits the pharmacology of an anesthetic competitive antagonist at the γ-aminobutyric acid type A receptor. Abstract : Naphthalene–etomidate only weakly potentiated γ-aminobutyric acid–evoked currents. However, it significantly decreased the positive modulatory effects of etomidate, propofol, and pentobarbital at the γ-aminobutyric acid type A receptor. The results suggest that naphthalene–etomidate acts as a competitive antagonist of anesthetics at the γ-aminobutyric acid type A receptor.